Green teens: Investigating the role of emotional intelligence in adolescent environmentalism. (1st February 2019) - Robinson, Alexia C.; Downey, Luke A.; Ford, Talitha C.; Lomas, Justine E.; Stough, Con
Abstract: Identifying the factors that drive environmentalism is critical to reduce human impact on the environment. Emotional intelligence (EI) has been shown to influence pro-environmental behaviour and environmental attitudes in adults, while such influences in adolescents are yet to be examined. The current study investigated the relationship between self-reported EI, pro-environmental attitude (PEA) and pro-environmental behaviour (PEB) in 382 Australian adolescents (12–17 years). Higher PEB was associated with higher PEA, and EI dimensions of Emotional Management and Control (EMC), and Understanding Others Emotions (UEO). Hierarchical multiple regression confirmed that PEA predicted PEB, while EMC also predicted PEB. EMC and UEO interactively moderated the relationship between PEA and PEB. This study suggests that adolescents' ability to manage, control and understand emotions affects the extent to which their PEAs predict PEBs, which has significant implications for the development of future environmental education initiatives to encourage pro-environmentalism.